Bush encroachment is a major handicap to livestock grazing in Tanzania - Louhaichi, Mounir (International Center for Agricultural Research in the Dry Areas, 2024)
Bush encroachment refers to the gradual invasion and expansion of woody vegetation into areas that were traditionally open for grazing. This encroachment negatively impacts the available grazing land for livestock, creating obstacles and difficulties for pastoral activities. the phot shows that the proliferation of bushes and shrubs is causing significant challenges for livestock grazing in Tanzania.